2014
DOI: 10.1080/08959420.2014.977662
|View full text |Cite
|
Sign up to set email alerts
|

Family Structure and Quality of Life of Elders in Rural China: The Role of the New Rural Social Pension

Abstract: Using data from a survey in Ankang district of Shaanxi province of China in 2011, this paper examines the protective effect of the NRSP on quality of life of the rural elderly, as well the moderating effect on association between family structure and quality of life. An instrumental variable approach is used. NRSP is shown to significantly improve the quality of life of rural elderly, and a robustness check shows that this effect is consistent across different sets of subgroups. Compared with the elderly who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…13 In T A B L E 2 Patients' mean scores of the Sleep Quality Index and the subscales in the Quality of Life Scale according to their socio-demographic characteristics (n = 212) another study on the matter, conducted with the elderly in China, it was reported that the quality of life of the elderly who have a large family and high level of social support is statistically significantly higher. 13 In T A B L E 2 Patients' mean scores of the Sleep Quality Index and the subscales in the Quality of Life Scale according to their socio-demographic characteristics (n = 212) another study on the matter, conducted with the elderly in China, it was reported that the quality of life of the elderly who have a large family and high level of social support is statistically significantly higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In T A B L E 2 Patients' mean scores of the Sleep Quality Index and the subscales in the Quality of Life Scale according to their socio-demographic characteristics (n = 212) another study on the matter, conducted with the elderly in China, it was reported that the quality of life of the elderly who have a large family and high level of social support is statistically significantly higher. 13 In T A B L E 2 Patients' mean scores of the Sleep Quality Index and the subscales in the Quality of Life Scale according to their socio-demographic characteristics (n = 212) another study on the matter, conducted with the elderly in China, it was reported that the quality of life of the elderly who have a large family and high level of social support is statistically significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2015 study examining the relationship between family structure and social support in the elderly, the authors reported that the extended family structure has a positive effect on quality of life. 13 In T A B L E 2 Patients' mean scores of the Sleep Quality Index and the subscales in the Quality of Life Scale according to their socio-demographic characteristics (n = 212) another study on the matter, conducted with the elderly in China, it was reported that the quality of life of the elderly who have a large family and high level of social support is statistically significantly higher. 14 In the same study, it was found that there was a significant difference between the mean quality of life psychological and social domains' scores of patients according to their family structure and the quality of life of patients with large family structure was higher.…”
Section: T a B L E 1 The Mean Scores Of Subscales Of The Quality Of Lmentioning
confidence: 99%
“…The general care of older people has traditionally been a family responsibility in Japan. However, changes in the family size and function have led to having fewer children and fewer family members being available to provide care for older people [24]. A previous study in Japan reported that older people who lived with a daughter had a reduced risk of being admitted to a geriatric institution [25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the NRPS has improved consumption among beneficiaries (Zheng and Zhong ), especially for elders with only one child (Liu et al. ). Cheng et al.…”
Section: Population Aging and The Nrps In Rural Chinamentioning
confidence: 99%